La sentinelle de l’écologie politique à l’aune de la démocratie locale : le cas de la Communauté urbaine de Bordeaux - Marième Pollèle Ndiaye; Gino Gramaccia (Communiquer)
How to implement environmental politics represents a considerable methodological challenge for local authorities. In this context, collective action appears as a strategic tool to stimulate territorial mobilization. But what logics guide environmental communication? How is it constructed? Through the example of a doctoral research conducted within the Urban Community of Bordeaux (UCB) between 2010 and 2013, the article examines the idea of “sentinel” in communication practices of local authorities. Also, it focuses on the importance of linking and territorial anchorage in the process of structuring public action.